ANALISIS KEUANGAN PUBLIK SYARIAH TERHADAP PENGELOLAAN ANGGARAN DAN PENGELUARAN PEMERINTAH DAERAH KULON PROGO - Mukti, Titania (I-Economics, 2023)
Management of regional budget and expenditure of Kulon Progo is the authority of regional governments and must be adapted to the conditions of regional communities. Financial management of a region has been taught in Islamic law since the time of the Prophet. The concept of regional financial management based on Islamic law must apply the principles of justice. The Kulon Progo Regency government is known to be the district with the smallest financial income/revenue among other districts in Yogyakarta. With small financial revenues, the government still has to distribute regional finances fairly. Therefore, this research aims to analyze the management of regional income and expenditure budgets in Kulon Progo Regency from an Islamic Public Finance Perspective for the 2022-2023 Period. The research method used descriptive qualitative analysis. The data source is primary data obtained from interviews with the local government of Kulon Progo Regency and several community representatives. The research results show that the stages of drafting the Kulon Progo Regency APBD draft are in accordance with the Processing Stage based on the provisions of law number 12 of 2019 concerning regional financial management. The process of tax revenue and regional expenditure determination in Kulon Progo has implemented Islamic public finance principles presented by Umar Chapra.